Solid Fuels from Decanter Cake and Other Palm Oil Industry Waste - Nugroho, Dewayanto; Mohd Haizal, Mohd Husin; Mohd Ridzuan, Nordin (Penerbit Universiti Teknologi Malaysia, 2015)
Palm oil milling plant generates about 4 – 5 wt % of decanter cake from the total weight of fresh fruit bunch processed. The decanter cake was dried overnight in an oven at 105 °C to reduce moisture content before it could be used as solid fuel. Thermogravimetry analysis, pyrolysis and combustion of the dried decanter cake were performed to characterise it. The proximate analysis indicated that the dried decanter cake contained 5 wt% moisture, 65 wt% volatile, 11 wt% fixed carbon and 19 wt% ash. The calorific value of the solid fuel from decanter cake was determined using oxygen bomb calorimeter. Its’ higher heating value (HHV) was determined to be 17.96 MJ/kg, comparable to that of other biomass either from palm oil waste or other agricultural waste. The solid fuel from decanter cake is found to be a suitable replacement for other biomass and coke based solid fuels.